National environment policy of Bangladesh: a crirical review - Akhtar, Md. Raihan (Institute of Governance Studies, BRAC University, 2013)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development (MAGD).